2019
DOI: 10.1089/neu.2018.5834
|View full text |Cite
|
Sign up to set email alerts
|

Extent of Spinal Cord Decompression in Motor Complete (American Spinal Injury Association Impairment Scale Grades A and B) Traumatic Spinal Cord Injury Patients: Post-Operative Magnetic Resonance Imaging Analysis of Standard Operative Approaches

Abstract: Although decompressive surgery following traumatic spinal cord injury (TSCI) is recommended, adequate surgical decompression is rarely verified via imaging. We utilized magnetic resonance imaging (MRI) to analyze the rate of spinal cord decompression after surgery. Pre-operative (within 8 h of injury) and post-operative (within 48 h of injury) MRI images of 184 motor complete patients (American Spinal Injury Association Impairment Scale [AIS] grade A = 119, AIS grade B = 65) were reviewed to verify spinal cord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(89 citation statements)
references
References 76 publications
2
83
0
4
Order By: Relevance
“…From this cohort, we screened and selected 72 patients who were eligible for this investigation. The inclusion criteria were being ‡16 years of age; Glasgow Coma Scale (GCS) score ‡14; no concurrent life-threatening injury or disease; imaging studies compatible with subaxial cervical spine fracture dislocations; available good quality pre-and post-operative computed tomography (CT) and MRI studies indicating complete spinal cord decompression following surgery; 35 and follow-up of at least 6 months after trauma and surgical management. The exclusion criteria were being obtunded, stuporous, and non-testable; having penetrating subaxial TSCI; having upper cervical SCI; a post-operative MRI indicating inadequate spinal cord decompression; non-operative management; having had a cervical CT myelogram and not an MRI as the primary imaging study; dying or being lost to follow-up; or having poorquality imaging studies.…”
Section: Cohortmentioning
confidence: 99%
See 3 more Smart Citations
“…From this cohort, we screened and selected 72 patients who were eligible for this investigation. The inclusion criteria were being ‡16 years of age; Glasgow Coma Scale (GCS) score ‡14; no concurrent life-threatening injury or disease; imaging studies compatible with subaxial cervical spine fracture dislocations; available good quality pre-and post-operative computed tomography (CT) and MRI studies indicating complete spinal cord decompression following surgery; 35 and follow-up of at least 6 months after trauma and surgical management. The exclusion criteria were being obtunded, stuporous, and non-testable; having penetrating subaxial TSCI; having upper cervical SCI; a post-operative MRI indicating inadequate spinal cord decompression; non-operative management; having had a cervical CT myelogram and not an MRI as the primary imaging study; dying or being lost to follow-up; or having poorquality imaging studies.…”
Section: Cohortmentioning
confidence: 99%
“…[25][26][27][28][29][30] Ongoing surgical studies on the relationship among imaging biomarkers, surgical strategy, and long-term clinical outcome are shaping the standard of care for these patients. 18,28,[31][32][33][34][35][36] Over the past 30 years, overarching evidence has supported spinal cord decompression following trauma, but the question of surgical timing has yet to be established within this evolving paradigm. 10,12,32,35,[37][38][39][40][41] In addition, although multiple reports have indicated that early anatomical alignment of the spinal column and decompression of the spinal cord followed by internal fixation is neuroprotective, in these studies, decompression of the spinal cord generally has not been verified by post-operative imaging.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…After TSCI, patients are transferred to neurosurgical or orthopedic units and most undergo spinal surgery to correct deformity and stabilize the fractured spine by placing screws, plates, and rods. Several surgical controversies exist, e.g., anterior versus posterior approach, number of levels to be fixed, timing of surgery, and the role of laminectomy [4][5][6][7][8][9][10]; thus, operative management largely relies on surgeons' preferences rather than robust evidence. Substantial literature has been devoted to the timing and role of surgery; currently, most surgeons opt for early surgery, once the patient is medically stable [8,10].…”
Section: Surgicalmentioning
confidence: 99%